Fenomena Munculnya Tokoh Islam Progresif Muhammadiyah 1980-2019 - Asep Sulaeman; Samsudin Samsudin (UIN Sunan Gunung Djati Bandung, 2021)
Since its first establishment until the productive contemporary period, Muhammadiyah have successfully generated noticeable figures who always oriented towards finding a path to the progress of Muslims. Some of Muhammadiyah progressive figures who are well known such as; M. Syafi'i Maarif and other associates. However, in the journey of contribution from their thoughts, they get criticized and cause controversy. It is believed that their thoughts are considered controversial and contrary to the tradition of thinking of the general public and lead to polemics among Indonesian Muslims. Even, these Muhammdiyah figures and their characters are often labelled as liberal figures who have ever been forbidden by MUI. Concerning this issue, the writers are interested in examining the issue by exploring main purposes: First, an overview progressive Islamic figures of Muhammadiyah. Second, what are the typology of progressive Islamic figures from Muhammadiyah? In this study the writers employed the historical method including heuristics, criticism or analysis, interpretation, and historiography. Based on the research results, the authors determined that the emergence of progressive Islam in contemporary period of Muhammadiyah produced many noticeable figures such as: Ahmad Syafii Maarif, Azyumardi Azra, Bahtiar Effendi, Dawam Raharjo, and Zuly Qadir. Second typology, in this term, progressive Islamic figures from Muhammadiyah are categorized into two typologies namely; Progressive-moderate and progressive-radical.